SURVEY AND EDUCATION HOW TO LIFT THE GOODS CORRECTLY ON FREIGHT FORWARDER IN BADUNG MARKET - wahyuni, nila (Buletin Udayana Mengabdi; Vol 19 No 3 (2020): Buletin Udayana Mengabdi, 2020)
Lifting loads on a freight forwarder is a manual material handling. If this activity is done incorrectly and repeatedly, it can become a risk factor for various musculoskeletal complaints. Various musculoskeletal complaints have been shown to cause various negative impacts on workers, namely a decrease in work productivity, an increase in health costs, a decrease in quality of life, etc. So it is very important to conduct education on correct manual material handling. The purpose of this activity is to increase the knowledge of how to lift weights properly and to provide an overview of risk factors and musculoskeletal complaints in freight forwarder in Badung market. The method that was used education using simple language and distributing brochures. Survey of musculoskeletal complaints was carried out by taking anamnesis and physical examination of the freight forwarder. Based on the survey results, most of the freight forwarder do not know how to lift the goods correctly. Most musculoskeletal complaints that freight forwarder suffered are neck, shoulder and upper back pain. This activity has a direct impact on freight forwarder because through this activity it can prevent occupational diseases of the freight forwarder in Badung market.